BETWEEN RACE; BEYOND RACE: THE EXPERIENCE OF SELF IDENTIFICATION OF INDIAN-WHITE BIRACIAL YOUNG ADULTS AND THE FACTORS AFFECTING THEIR CHOICES OF IDENTITY - Francis, Dennis (PINS-Psychology in Society, 2025)
This study, based on my doctoral research, is an exploration of how nine Indian-White biracial young adults interpret their social reality, especially with regard to their understanding and experience of racial identity. I chose life histories as a method in line with my view of social identity as a resource that people draw on in constructing personal narratives, which provide meaning and a sense of continuity to their lives. As a life history researcher I started with the assumption that by asking the participants to tell me stories of their lives I would gain access to how biracial young adults interpret their social world and what they believe about themselves. All of the primary research took place within the Durban area. In giving an account of their identities, the nine biracial young adults in my study described their life worlds as the sum of many parts, which included but was not limited to their racial identity. With regards to racial identity, the participants chose a variety of ways to name themselves. Four self-identified as Indian, one chose not to place himself into a racial category, and four named themselves as Indian and White or mixed race. None of the nine Indian-White biracial young adults in my study named themselves as White, and none identified themselves as Coloured. The participants named a combination of factors as influencing how they identified – at times these were not without inconsistencies and contradictions. While some factors were more salient than others, I argue that no single factor that influences identity can be looked at in isolation or as assumed to be more important from any other. In their account of the various factors that contributed to their understanding of racial identity, none of the participants identified their assigned racial classification as having a direct influence on their choice of racial identity.